Efficacy and safety of acupuncture for chronic pain caused by gonarthrosis: A study protocol of an ongoing multi-centre randomised controlled clinical trial [ISRCTN27450856] - Streitberger, Konrad (BioMed Central, 2004)
BACKGROUND: Controlled clinical trials produced contradictory results with respect to a specific analgesic effect of acupuncture. There is a lack of large multi-centre acupuncture trials. The German Acupuncture Trial represents the largest multi-centre study of acupuncture in the treatment of chronic pain caused by gonarthrosis up to now. METHODS: 900 patients will be randomised to three treatment arms. One group receives verum acupuncture, the second sham acupuncture, and the third conservative standard therapy. The trial protocol is described with eligibility criteria, detailed information on the treatment definition, blinding, endpoints, safety evaluation, statistical methods, sample size determination, monitoring, legal aspects, and the current status of the trial. DISCUSSION: A critical discussion is given regarding the considerations about standardisation of the acupuncture treatment, the choice of the control group, and the blinding of patients and observers.